Pencegahan Gangguan Fungsi Ginjal Karena Stres Oksidatif pada Tikus Diabetes dengan Ubi Jalar Ungu - Jawi, I Made; Sumardika, I Wayan; Linawati, Ni Made (Jurnal Veteriner, 2014)
Recently, anthocyanins-rich food, is believed to prevent tissue damages due to oxidative stress. This studyaimed to investigate the protective effect of water extract of Balinese purple sweet potatoes which containhigh anthocyanins to the renal tissues of diabetic rats. A total of 30 adult male rats were divided into threegroups using randomized post-test only control group design, respectivelly. Animals in group 1 (diabeticgroup) were given streptozotocin 60 mg/kg; group 2 (diabetic+extract/ treatment group) at 3 days after theanimals were given streptozotocin they were given 4 mL per day of the extract for 50, group 3 (control group)animals were given placebo. At day 50 of the treatment, the blood and renal tissue superoxidase dismutase(SOD) and malondialdehyde (MDA), creatinin and blood urea nitrogen (BUN) level of all rats were measured.The data were analyzed using analysis of variance. The results showed a significant increase of blood andrenal tissues MDA and BUN level in group 1 (p<0,05). In addition, a decrease of SOD and creatinin level(p<0,05) were also seen in this group. In comparison to animals in group 2, the increase of blood MDA andBUN level as well the decrease of SOD and, creatinin level were significantly lower (p<0,05). From thesefindings, it can be concluded that aqueous extract of Balinese purple sweet potato can prevent renalfunction disorders due to oxidative stress.
Keywords: Balinese purple sweet potato, oxidative stress, renal tissue, diabetic rats